PENGARUH KONTRIBUSI DAN EFEKTIVITAS PAJAK HOTEL TERHADAP PENDAPATAN ASLI DAERAH KOTA BATAM - Dwiyanti, Futri; Handra Tipa (LPPM Universitas Putera Batam, 2022)
The biggest potential of the City of Batam in financing regional expenditures comes from local taxes and is expected to be able to provide the largest contribution to PAD. This study aims to determine the effectiveness of hotel tax collection and its contribution to PAD in Batam City. The data analysis method in this research is descriptive analysis. The variables in this study are effectiveness and contribution analysis. The data analysis technique in this research is quantitative analysis. Based on the results of the analysis, the average effectiveness of Batam City hotel tax collection in 2016-2020 has been effective and the average contribution of Batam City hotel tax collection in 2016-2020 is not very good.Keywords: effectiveness, contribution, hotel tax, local revenue